An Evolving View of Phylogenetic Support. (11th September 2020) - Simon, Chris
Abstract: If all nucleotide sites evolved at the same rate within molecules and throughout the history of lineages, if all nucleotides were in equal proportion, if any nucleotide or amino acid evolved to any other with equal probability, if all taxa could be sampled, if diversification happened at well-spaced intervals, and if all gene segments had the same history, then tree building would be easy. But of course, none of those conditions are true. Hence, the need for evaluating the information content and accuracy of phylogenetic trees. The symposium for which this historical essay and presentation were developed focused on the importance of phylogenetic support, specifically branch support for individual clades. Here, I present a timeline and review significant events in the history of systematics that set the stage for the development of the sophisticated measures of branch support and examinations of the information content of data highlighted in this symposium. [Bayes factors; bootstrap; branch support; concordance factors; internode certainty; posterior probabilities; spectral analysis; transfer bootstrap expectation.]